(untitled) (Stato, Chiese e pluralismo confessionale, 2021)
SOMMARIO: 1. Introduzione - 2. La religious accommodation in Europa - 3. (segue) Gli sviluppi più recenti - 4. Il ruolo della giurisprudenza europea: primi segnali di apertura all’accomodamento religioso - 5. Il know-how statunitense e canadese: modelli giurisprudenziali a confronto e possibili interazioni - 6. La religious accommodation in Europa: una prospettiva de iure condendo. The European frontiers of religious accommodation. Starting points for comparison ABSTRACT: In the last years several scholars pointed out the desirability to extend the accommodation beyond disability. Currently, indeed, a duty of reasonable accommodation is exclusively provided in favour of people with disabilities (art. 5 dir. 2000/78/CE). Previous contributions, however, have stressed how the existing lack of a provision on religious accommodation can result not only in a low level of protection of religious freedom, but also in the rise of a hierarchy related to discrimination grounds in which religion and belief seem to be left at the bottom. Recently, also the European Courts (especially the ECtHR) have apparently open to the extension of the concept of reasonable accommodation, in line with the sensitivity of the Supreme Courts of USA and Canada, where the religious accommodation was first stated. Moving from the comparison between the American and Canadian jurisprudences and the European one, this paper argues about the transposability of the religious accommodation in Europe, in order to strengthen, even in the workplace, the protection of the freedom of religion.